Problem of Apollonius

From Math Images

(Difference between revisions)
Jump to: navigation, search
Current revision (12:26, 2 July 2012) (edit) (undo)
 
(38 intermediate revisions not shown.)
Line 1: Line 1:
-
{{Image Description
+
{{Image Description Ready
 +
|Field=Geometry
 +
|Field2=Fractals
|ImageName=Apollonian Gasket
|ImageName=Apollonian Gasket
|Image=Apollonian.jpg
|Image=Apollonian.jpg
 +
|AuthorName=Paul Nylander
 +
|SiteName=Fractals
 +
|Field=Fractals
 +
|Field=Geometry
 +
|SiteURL=http://bugman123.com/Fractals/Fractals.html
 +
|InProgress=No
|ImageIntro=This an example of a fractal that can be created by repeatedly solving the Problem of Apollonius.
|ImageIntro=This an example of a fractal that can be created by repeatedly solving the Problem of Apollonius.
|ImageDescElem=<div style="width:auto; position:relative;">[[Image:Apollonius.png|thumb|150px|Image by: [http://commons.wikimedia.org/wiki/File:Apollonius_solution_3B.png Wikipedia]|left]]<div style="position:relative;">The problem of Apollonius involves trying to find a circle that is tangent to three objects: points, lines, or circles in a plane. The most famous of these is the case involving three different circles in a plane, as seen in the picture to the left. The given three circles are in red, green, and blue, while the solution circle is in black.</div></div>
|ImageDescElem=<div style="width:auto; position:relative;">[[Image:Apollonius.png|thumb|150px|Image by: [http://commons.wikimedia.org/wiki/File:Apollonius_solution_3B.png Wikipedia]|left]]<div style="position:relative;">The problem of Apollonius involves trying to find a circle that is tangent to three objects: points, lines, or circles in a plane. The most famous of these is the case involving three different circles in a plane, as seen in the picture to the left. The given three circles are in red, green, and blue, while the solution circle is in black.</div></div>
Line 13: Line 21:
Given three points, the problem only has one solution. In the cases of one line and two points; two lines and one point; and one circle and two points, the problem has two solutions. Four solutions exist for the cases of three lines; one circle, one line, and one point; and two circles and one point. There are eight solutions for the cases of two circles and one line; and one circle and two lines, in addition to the three circle problem.
Given three points, the problem only has one solution. In the cases of one line and two points; two lines and one point; and one circle and two points, the problem has two solutions. Four solutions exist for the cases of three lines; one circle, one line, and one point; and two circles and one point. There are eight solutions for the cases of two circles and one line; and one circle and two lines, in addition to the three circle problem.
-
{{-}}
+
|ImageDesc=
-
 
+
-
<h1> A More Mathematical Explanation</h1>
+
There are many different ways of solving the problem of Apollonius. The few that are easiest to understand include using an algebraic method or an [[Inversion|inverse geometry]] method.
There are many different ways of solving the problem of Apollonius. The few that are easiest to understand include using an algebraic method or an [[Inversion|inverse geometry]] method.
-
 
-
{{-}}
 
=== Algebraic Method ===
=== Algebraic Method ===
-
{{hide|1=This method only uses math up to the level of understanding quadratic equations. We will proceed by setting up a system of quadratic equations and solving for the radius, r, of the unknown circle.
+
This method only uses math up to the level of understanding quadratic equations. We will proceed by setting up a system of quadratic equations and solving for the radius, r, of the unknown circle.
We start by labeling the center of each of the given circles <math>(x</math><sub>1</sub><math>,y</math><sub>1</sub><math>)</math>, <math>(x</math><sub>2</sub><math>,y</math><sub>2</sub><math>)</math>, and <math>(x</math><sub>3</sub><math>,y</math><sub>3</sub><math>)</math>. We will call the center of the unknown circle <math>(x,y)</math>. <math>r</math><sub>1</sub>,<math>r</math><sub>2</sub>, and <math>r</math><sub>3</sub> are the different radii of each of the given circles.
We start by labeling the center of each of the given circles <math>(x</math><sub>1</sub><math>,y</math><sub>1</sub><math>)</math>, <math>(x</math><sub>2</sub><math>,y</math><sub>2</sub><math>)</math>, and <math>(x</math><sub>3</sub><math>,y</math><sub>3</sub><math>)</math>. We will call the center of the unknown circle <math>(x,y)</math>. <math>r</math><sub>1</sub>,<math>r</math><sub>2</sub>, and <math>r</math><sub>3</sub> are the different radii of each of the given circles.
Line 39: Line 43:
:*<math>(x^2+y^2-r^2)-2xx</math><sub>1</sub><math>-2yy</math><sub>1</sub><math>\pm2rr</math><sub>1</sub><math>+(x</math><sub>1</sub><math>^2+y</math><sub>1</sub><math>^2-r</math><sub>1</sub><math>^2)=0</math>
:*<math>(x^2+y^2-r^2)-2xx</math><sub>1</sub><math>-2yy</math><sub>1</sub><math>\pm2rr</math><sub>1</sub><math>+(x</math><sub>1</sub><math>^2+y</math><sub>1</sub><math>^2-r</math><sub>1</sub><math>^2)=0</math>
:*<math>(x^2+y^2-r^2)-2xx</math><sub>2</sub><math>-2yy</math><sub>2</sub><math>\pm2rr</math><sub>2</sub><math>+(x</math><sub>2</sub><math>^2+y</math><sub>2</sub><math>^2-r</math><sub>2</sub><math>^2)=0</math>
:*<math>(x^2+y^2-r^2)-2xx</math><sub>2</sub><math>-2yy</math><sub>2</sub><math>\pm2rr</math><sub>2</sub><math>+(x</math><sub>2</sub><math>^2+y</math><sub>2</sub><math>^2-r</math><sub>2</sub><math>^2)=0</math>
-
:*<math>(x^2+y^2-r^2)-2xx</math><sub>3</sub><math>-2yy</math><sub>3</sub><math>\pm2rr</math><sub>3</sub><math>+(x</math><sub>3</sub><math>^2+y</math><sub>3</sub><math>^2-r</math><sub>3</sub><math>^2)=0</math>}}
+
:*<math>(x^2+y^2-r^2)-2xx</math><sub>3</sub><math>-2yy</math><sub>3</sub><math>\pm2rr</math><sub>3</sub><math>+(x</math><sub>3</sub><math>^2+y</math><sub>3</sub><math>^2-r</math><sub>3</sub><math>^2)=0</math>
We can now look at the equations and see how we can subtract them from each other. So we will take the second and third equation minus the first equation.
We can now look at the equations and see how we can subtract them from each other. So we will take the second and third equation minus the first equation.
Line 45: Line 49:
Second minus first gives us:
Second minus first gives us:
-
:*<math>2(x</math><sub>1</sub><math>-x</math><sub>2</sub><math>)x+2(y</math><sub>1</sub><math>-y</math><sub>2</sub><math>)+2(\pmr</math><sub>1</sub><math>\pm</math><sub>2</sub>)r=(x<sub>1</sub>^2+y<sub>1</sub>^2-r<sub>1</sub>^2)-(x<sub>2</sub>^2+y<sub>2</sub>^2-r<sub>2</sub>^2)
+
:*<math> 2(x_1-x_2)x+2(y_1-y_2)y+2(\pm r_1 \pm r_2)r=(x_1^2+y_1^2-r_1^2)-(x_2^2+y_2^2-r_2^2) </math>
 +
Third minus first gives us:
 +
:*<math> 2(x_1-x_3)x+2(y_1-y_3)y+2(\pm r_1 \pm r_3)r=(x_1^2+y_1^2-r_1^2)-(x_3^2+y_3^2-r_3^2) </math>
-
<h1> Apollonian Gasket </h1>
+
For the sake of simplicity, we'll define some new variables. Let
-
{{Switch|link1=Show|link2=Hide|1=<div style="float:left; margin-right:25px"><pausegif id="2" wiki="no" border="no">Problemapollonius3.gif</pausegif></div>|2=The Apollonian gasket is an example of one of the earliest studied fractals and was first constructed by Gottfried Leibniz. It can be constructed by solving the problem of Apollonius iteratively. It was a precursor to [[Sierpinski's Triangle]], and in a special case, it forms [[Ford Circles]].
+
 
 +
<math> a_2=2(x_1-x_2) </math>; <math> b_2=2(y_1-y_2)</math> ; <math> c_2=2(\pm r_1 \pm r_2) </math> ; <math>d_2=(x_1^2+y_1^2-r_1^2)-(x_2^2+y_2^2-r_2^2) </math>
 +
 
 +
<math> a_3=2(x_1-x_3) </math>; <math> b_3=2(y_1-y_3)</math> ; <math> c_3=2(\pm r_1 \pm r_3) </math> ; <math>d_2=(x_1^2+y_1^2-r_1^2)-(x_3^2+y_3^2-r_3^2) </math>
 +
 
 +
Now our two equations can be written as
 +
:<math> a_2 x+b_2 y +c_2 r=d_2 </math>
 +
:<math> a_3 x+b_3 y +c_3 r=d_3 </math>
 +
 
 +
Since this is a simple linear system of equations, we can solve it for x and y in terms of r.
 +
{{Switch|link1=click to show algebra |link2=click to hide algebra|1=|2=
 +
 
 +
Solving the first equation for x:
 +
<math> a_2x=d_2-c_2r-b_2y \rightarrow x=\frac{d_2-c_2 r -b_2 y}{a_2} </math>
 +
 
 +
Substituting that in to the second equation allows us to find y in terms of known values and r:
 +
 
 +
<math> a_3\left(\frac{d_2-c_2 r -b_2 y}{a_2} \right)+b_3 y +c_3 r =d_3 </math>
 +
 
 +
<math> a_3 d_2-a_3c_2 r -a_3 b_2 y+a_2 b_3 y +a_2 c_3 r =d_3 a_2 </math>
 +
 
 +
<math> y(a_2 b_3-a_3 b_2)=a_2 d_3-a_3 d_2 +(a_3 c_2 -a_2 c_3)r </math>
 +
 
 +
*<math> y=\frac{a_2 d_3-a_3 d_2 +(a_3 c_2 -a_2 c_3)r}{a_2 b_3-a_3 b_2} </math>.
 +
 
 +
Rather than substituting back in to find x, it is actually simpler to go through the same process we used to find y to get x in terms of known values and r.
 +
 
 +
First, we solve the first equation for y.
 +
 
 +
<math> b_2y=d_2-c_2r-a_2x \rightarrow y=\frac{d_2-c_2 r -a_2 x}{b_2} </math>
 +
 
 +
Plugging into the second equation gives us
 +
 
 +
<math> a_3 x+b_3\left(\frac{d_2-c_2 r -a_2 x}{b_2}\right) +c_3 r =d_3 </math>
 +
 
 +
<math> a_3 b_2 x+b_3 d_2 -b_3 c_2 r-a_2 b_3 x +b_2 c_3 r=b_2 d_3 </math>
 +
 
 +
<math> x(a_3 b_2-a_2 b_3)=b_2 d_3-b_3 d_2 +(b_3 c_2-b_2 c_3) r </math>
 +
 
 +
*<math> x=\frac{b_2 d_3-b_3 d_2 +(b_3 c_2-b_2 c_3) r}{a_3 b_2-a_2 b_3} </math>.}}
 +
 
 +
With <math> x=\frac{b_2 d_3-b_3 d_2 +(b_2 c_3-b_3 c_2) r}{a_3 b_2-a_2 b_3} </math> and <math> y=\frac{a_2 d_3-a_3 d_2 +(a_3 c_2 -a_2 c_3)r}{a_2 b_3-a_3 b_2} </math>, we plug in values for the a's, b's and c's (which we get from the original information about the centers and radii of the three circles) to calculate x and y. Using our very first equations for the circles, we can then solve for r.
 +
 
 +
{{Switch|link1=click to show example|link2=click to hide example|1=|2=
 +
 
 +
Let's pick three circles and find the mutually tangent ones. Let's choose some coordinates and radii for our three circles.
 +
 
 +
Take <math> (x_1,y_1,r_1)=(0,3,2) </math>, <math> (x_2,y_2,r_2)=(-2,-2,1) </math> and <math> (x_3,y_3,r_3)=(3,-3,3)</math>. These three circles are shown below.
 +
 
 +
[[Image:Circleex1.png|300]]
 +
 
 +
Now we want to calculate the a's, b's, and d's first.
 +
 
 +
<math> a_2=2(x_1-x_2)=2(0--2)=4</math>
 +
 
 +
<math> a_3=2(x_1-x_3)=2(0-3)=-6</math>
 +
 
 +
<math> b_2=2(y_1-y_2)=2(3--2)=10</math>
 +
 
 +
<math> b_3=2(y_1-y_3)=2(3--3)=12</math>
 +
 
 +
<math> d_2=(x_1^2+y_1^2-r_1^2)-(x_2^2+y_2^2-r_2^2) =(0^2+3^2-2^2)-(2^2+2^2-1^2)=(9-4)-(4+4-1)=-2 </math>
 +
 
 +
<math> d_3=(x_1^2+y_1^2-r_1^2)-(x_3^2+y_3^2-r_3^2) =(0^2+3^2-2^2)-(3^2+3^2-3^2)=(9-4)-(9+9-9)=-4 </math>
 +
 
 +
Calculating the c terms requires a bit more thought since there are the <math> \pm </math> signs. The choice of these signs determines which circle we are solving for. We simply must be consistent in all of our applications of signs for a given r. For the first example, let's simply take all of the plus signs. Then
 +
 
 +
<math> c_2=2(r_1+r_2)=2(2+1)=6</math>
 +
 
 +
<math> c_3=2(r_1+r_3)=2(2+3)=10 </math>.
 +
 
 +
Now we can calculate x and y for this first circle.
 +
 
 +
<math>x=\frac{b_2 d_3-b_3 d_2 +(b_3 c_2-b_2 c_3) r}{a_3 b_2-a_2 b_3}=\frac{(10)(-4)-(12)(-2)+(12(6)-10(10))r}{-6(10)-4(12)}=\frac{-16-(28)r}{-108} </math>
 +
 
 +
<math> x=\frac{1}{27}(4+7r) </math>.
 +
 
 +
<math>y=\frac{a_2 d_3-a_3 d_2 +(a_3 c_2 -a_2 c_3)r}{a_2 b_3-a_3 b_2}=\frac{(4)(-4)-(-6)(2)+ (-6(6)-4(10))r}{12(4)-(10)(-6)}=\frac{-28-(76)r}{108} </math>
 +
 
 +
<math> y=\frac{-7-19r}{27} </math>.
 +
 
 +
Now we can return to one of our first equations to find r.
 +
 
 +
<math> (x-x_1)^2+(y-y_1)^2=(r+r_1)^2 </math>
 +
 
 +
Note that here the sign of <math> r_1 </math> is positive. That is because we took the positive sign when we solved for the c values. Plugging in values, we get
 +
 
 +
<math> \left(\frac{1}{27}(4+7r)\right)^2+\left(\frac{-7-19r}{27}-3 \right)^2=(r+2)^2 </math>
 +
 
 +
This equation is quadratic in r, so it can be solved using the quadratic formula (or a graphing calculator, if you prefer). When the dust clears, we get <math> r\approx 4.729 </math> (the other value that comes out of the quadratic formula does not work when plotted).
 +
 
 +
Now we can plot this circle with center <math> \left(\frac{1}{27}(4+7(4.729)),\frac{-7-19(4.729)}{27} \right) </math>. It is shown below in red, with the original circles in black.
 +
 
 +
[[Image:Circleex2.png|300px|center]]
 +
 
 +
We can see that it is indeed tangent to the three original circles!
 +
 
 +
This process can be repeated choosing different signs for the different r values in the c coefficients to find the other seven circles.
 +
 
 +
}}
 +
 
 +
 
 +
 
 +
 
 +
== Apollonian Gasket ==
 +
The Apollonian gasket is an example of one of the earliest studied fractals and was first constructed by Gottfried Leibniz. It can be constructed by solving the problem of Apollonius iteratively. It was a precursor to [[Sierpinski's Triangle]], and in a special case, it forms [[Ford Circles]].
<div style="float:left"><pausegif id="2" wiki="no" border="no">Problemapollonius3.gif</pausegif></div>
<div style="float:left"><pausegif id="2" wiki="no" border="no">Problemapollonius3.gif</pausegif></div>
Line 62: Line 173:
Repeating this process over and over again with each set of three mutually tangent circles will create the Apollonian gasket.}}
Repeating this process over and over again with each set of three mutually tangent circles will create the Apollonian gasket.}}
-
{{-}}
+
== Interactive Applet ==
 +
{{#iframe:https://www.cs.drexel.edu/~rlw82/Canvas/ResizeCircles/|632|632|border=0}}
 +
<BR>
 +
Drag the circles around for solutions to be drawn
 +
Drag the red circles to resize that circle
 +
 
 +
== References ==
 +
 
-
<h1>References</h1>
 
Math Pages, [http://www.mathpages.com/HOME/kmath113.htm Apollonius' Tangency Problem]
Math Pages, [http://www.mathpages.com/HOME/kmath113.htm Apollonius' Tangency Problem]
Line 70: Line 187:
MathWorld, [http://mathworld.wolfram.com/ApolloniusProblem.html Apollonius' Problem]
MathWorld, [http://mathworld.wolfram.com/ApolloniusProblem.html Apollonius' Problem]
 +
Wikibooks , [http://en.wikibooks.org/wiki/Fractals/Apollonian_fractals Apollonian fractals]
 +
== Mathematica Programs ==
 +
[[User:AnnaP|Anna]] created several programs that solve the problem of Apollonius in the case of three non-tangent, non-intersecting circles that the user inputs. The programs were written in Mathematica 7, but are likely compatible with Mathematica 5 and/or 6.
-
|AuthorName=Paul Nylander
+
The first program automatically plots all eight solutions. [http://www.sccs.swarthmore.edu/users/09/anna09/mathematica/apolloniussolution.nb Click here to download this program]
-
|SiteName=Fractals
+
 
-
|SiteURL=http://bugman123.com/Fractals/Fractals.html
+
The second program allows the user to choose which solutions to plot in groups of two. [http://www.sccs.swarthmore.edu/users/09/anna09/mathematica/apolloniussolutionoptions.nb Click here to download this program]
-
|Field=Geometry
+
-
|Field2=Fractals
+
-
|InProgress=Yes
+
-
}}
+

Current revision


Apollonian Gasket
Fields: Geometry and Fractals
Image Created By: Paul Nylander
Website: Fractals

Apollonian Gasket

This an example of a fractal that can be created by repeatedly solving the Problem of Apollonius.


Contents

Basic Description

Image by: Wikipedia
Image by: Wikipedia
The problem of Apollonius involves trying to find a circle that is tangent to three objects: points, lines, or circles in a plane. The most famous of these is the case involving three different circles in a plane, as seen in the picture to the left. The given three circles are in red, green, and blue, while the solution circle is in black.


Apollonius of Perga posed and solved this problem in his work called Tangencies. Sadly, Tangencies has been lost, and only a report of his work by Pappus of Alexandria is left. Since then, other mathematicians, such as Isaac Newton and Descartes, have been able to recreate his results and discover new ways of solving this interesting problem.


Click to stop animation.
The problem usually has eight different solution circles that exist that are tangent to the given three circles in a plane. The given circles must not be tangent to each other, overlapping, or contained within one another for all eight solutions to exist.


Given three points, the problem only has one solution. In the cases of one line and two points; two lines and one point; and one circle and two points, the problem has two solutions. Four solutions exist for the cases of three lines; one circle, one line, and one point; and two circles and one point. There are eight solutions for the cases of two circles and one line; and one circle and two lines, in addition to the three circle problem.

A More Mathematical Explanation

There are many different ways of solving the problem of Apollonius. The few that are easiest to under [...]

There are many different ways of solving the problem of Apollonius. The few that are easiest to understand include using an algebraic method or an inverse geometry method.

Algebraic Method

This method only uses math up to the level of understanding quadratic equations. We will proceed by setting up a system of quadratic equations and solving for the radius, r, of the unknown circle.

We start by labeling the center of each of the given circles (x1,y1), (x2,y2), and (x3,y3). We will call the center of the unknown circle (x,y). r1,r2, and r3 are the different radii of each of the given circles.

From this we are able to write our equations:

  • (x - x1)^2 + (y - y1)^2 = (r \pm r1)^2
  • (x - x2)^2 + (y - y2)^2 = (r \pm r2)^2
  • (x - x3)^2 + (y - y3)^2 = (r \pm r3)^2

Next we are able to expand each of the equations to see better how they can relate to each other.

Expanding gives us:

  • (x^2+y^2-r^2)-2xx1-2yy1\pm2rr1+(x1^2+y1^2-r1^2)=0
  • (x^2+y^2-r^2)-2xx2-2yy2\pm2rr2+(x2^2+y2^2-r2^2)=0
  • (x^2+y^2-r^2)-2xx3-2yy3\pm2rr3+(x3^2+y3^2-r3^2)=0

We can now look at the equations and see how we can subtract them from each other. So we will take the second and third equation minus the first equation.

Second minus first gives us:

  •  2(x_1-x_2)x+2(y_1-y_2)y+2(\pm r_1 \pm r_2)r=(x_1^2+y_1^2-r_1^2)-(x_2^2+y_2^2-r_2^2)

Third minus first gives us:

  •  2(x_1-x_3)x+2(y_1-y_3)y+2(\pm r_1 \pm r_3)r=(x_1^2+y_1^2-r_1^2)-(x_3^2+y_3^2-r_3^2)

For the sake of simplicity, we'll define some new variables. Let

 a_2=2(x_1-x_2) ;  b_2=2(y_1-y_2)  ;  c_2=2(\pm r_1 \pm r_2)  ; d_2=(x_1^2+y_1^2-r_1^2)-(x_2^2+y_2^2-r_2^2)

 a_3=2(x_1-x_3) ;  b_3=2(y_1-y_3)  ;  c_3=2(\pm r_1 \pm r_3)  ; d_2=(x_1^2+y_1^2-r_1^2)-(x_3^2+y_3^2-r_3^2)

Now our two equations can be written as

 a_2 x+b_2 y +c_2 r=d_2
 a_3 x+b_3 y +c_3 r=d_3

Since this is a simple linear system of equations, we can solve it for x and y in terms of r.

Solving the first equation for x:

 a_2x=d_2-c_2r-b_2y \rightarrow x=\frac{d_2-c_2 r -b_2 y}{a_2}

Substituting that in to the second equation allows us to find y in terms of known values and r:

 a_3\left(\frac{d_2-c_2 r -b_2 y}{a_2} \right)+b_3 y +c_3 r =d_3

 a_3 d_2-a_3c_2 r -a_3 b_2 y+a_2 b_3 y +a_2 c_3 r =d_3 a_2

 y(a_2 b_3-a_3 b_2)=a_2 d_3-a_3 d_2 +(a_3 c_2  -a_2 c_3)r

  •  y=\frac{a_2 d_3-a_3 d_2 +(a_3 c_2  -a_2 c_3)r}{a_2 b_3-a_3 b_2} .

Rather than substituting back in to find x, it is actually simpler to go through the same process we used to find y to get x in terms of known values and r.

First, we solve the first equation for y.

 b_2y=d_2-c_2r-a_2x \rightarrow y=\frac{d_2-c_2 r -a_2 x}{b_2}

Plugging into the second equation gives us

 a_3 x+b_3\left(\frac{d_2-c_2 r -a_2 x}{b_2}\right) +c_3 r =d_3

 a_3 b_2 x+b_3 d_2 -b_3 c_2 r-a_2 b_3 x +b_2 c_3 r=b_2 d_3

 x(a_3 b_2-a_2 b_3)=b_2 d_3-b_3 d_2 +(b_3 c_2-b_2 c_3) r

  •  x=\frac{b_2 d_3-b_3 d_2 +(b_3 c_2-b_2 c_3) r}{a_3 b_2-a_2 b_3} .


With  x=\frac{b_2 d_3-b_3 d_2 +(b_2 c_3-b_3 c_2) r}{a_3 b_2-a_2 b_3} and  y=\frac{a_2 d_3-a_3 d_2 +(a_3 c_2  -a_2 c_3)r}{a_2 b_3-a_3 b_2} , we plug in values for the a's, b's and c's (which we get from the original information about the centers and radii of the three circles) to calculate x and y. Using our very first equations for the circles, we can then solve for r.

Let's pick three circles and find the mutually tangent ones. Let's choose some coordinates and radii for our three circles.

Take  (x_1,y_1,r_1)=(0,3,2) ,  (x_2,y_2,r_2)=(-2,-2,1) and  (x_3,y_3,r_3)=(3,-3,3). These three circles are shown below.

300

Now we want to calculate the a's, b's, and d's first.

 a_2=2(x_1-x_2)=2(0--2)=4

 a_3=2(x_1-x_3)=2(0-3)=-6

 b_2=2(y_1-y_2)=2(3--2)=10

 b_3=2(y_1-y_3)=2(3--3)=12

 d_2=(x_1^2+y_1^2-r_1^2)-(x_2^2+y_2^2-r_2^2) =(0^2+3^2-2^2)-(2^2+2^2-1^2)=(9-4)-(4+4-1)=-2

 d_3=(x_1^2+y_1^2-r_1^2)-(x_3^2+y_3^2-r_3^2) =(0^2+3^2-2^2)-(3^2+3^2-3^2)=(9-4)-(9+9-9)=-4

Calculating the c terms requires a bit more thought since there are the  \pm signs. The choice of these signs determines which circle we are solving for. We simply must be consistent in all of our applications of signs for a given r. For the first example, let's simply take all of the plus signs. Then

 c_2=2(r_1+r_2)=2(2+1)=6

 c_3=2(r_1+r_3)=2(2+3)=10 .

Now we can calculate x and y for this first circle.

x=\frac{b_2 d_3-b_3 d_2 +(b_3 c_2-b_2 c_3) r}{a_3 b_2-a_2 b_3}=\frac{(10)(-4)-(12)(-2)+(12(6)-10(10))r}{-6(10)-4(12)}=\frac{-16-(28)r}{-108}

 x=\frac{1}{27}(4+7r) .

y=\frac{a_2 d_3-a_3 d_2 +(a_3 c_2  -a_2 c_3)r}{a_2 b_3-a_3 b_2}=\frac{(4)(-4)-(-6)(2)+ (-6(6)-4(10))r}{12(4)-(10)(-6)}=\frac{-28-(76)r}{108}

 y=\frac{-7-19r}{27} .

Now we can return to one of our first equations to find r.

 (x-x_1)^2+(y-y_1)^2=(r+r_1)^2

Note that here the sign of  r_1 is positive. That is because we took the positive sign when we solved for the c values. Plugging in values, we get

 \left(\frac{1}{27}(4+7r)\right)^2+\left(\frac{-7-19r}{27}-3 \right)^2=(r+2)^2

This equation is quadratic in r, so it can be solved using the quadratic formula (or a graphing calculator, if you prefer). When the dust clears, we get  r\approx 4.729 (the other value that comes out of the quadratic formula does not work when plotted).

Now we can plot this circle with center  \left(\frac{1}{27}(4+7(4.729)),\frac{-7-19(4.729)}{27} \right) . It is shown below in red, with the original circles in black.

We can see that it is indeed tangent to the three original circles!

This process can be repeated choosing different signs for the different r values in the c coefficients to find the other seven circles.




Apollonian Gasket

The Apollonian gasket is an example of one of the earliest studied fractals and was first constructed by Gottfried Leibniz. It can be constructed by solving the problem of Apollonius iteratively. It was a precursor to Sierpinski's Triangle, and in a special case, it forms Ford Circles.

Click to stop animation.


Constructing the gasket begins with three mutually tangent circles. By solving this case of the problem of Apollonius we know that there are two other circles that are tangent to the three given circles. We now have five circles from which to start again.


Repeat the process with two of the original circles and one of the newly generated circles. Again, by solving Apollonius' problem we can find two circles that are tangent to this new set of three circles. Although, we already know one of the two solutions for this set of three circles; it is the other of the three circles that we started with.


Repeating this process over and over again with each set of three mutually tangent circles will create the Apollonian gasket.




Teaching Materials

There are currently no teaching materials for this page. Add teaching materials.









If you are able, please consider adding to or editing this page!

Have questions about the image or the explanations on this page?
Leave a message on the discussion page by clicking the 'discussion' tab at the top of this image page.






Interactive Applet


Drag the circles around for solutions to be drawn Drag the red circles to resize that circle

References

Math Pages, Apollonius' Tangency Problem

MathWorld, Apollonius' Problem

Wikibooks , Apollonian fractals

Mathematica Programs

Anna created several programs that solve the problem of Apollonius in the case of three non-tangent, non-intersecting circles that the user inputs. The programs were written in Mathematica 7, but are likely compatible with Mathematica 5 and/or 6.

The first program automatically plots all eight solutions. Click here to download this program

The second program allows the user to choose which solutions to plot in groups of two. Click here to download this program

Personal tools